115. Opioid Continuum of Care for Persons Living with HIV: The First 8 Months. (31st December 2020) - Eaton, Ellen; Hunt, Paula; Turner, Orlando; Raper, James; Saag, Michael
Abstract: Background: Approximately 15% of persons with HIV (PWH) have opioid use disorder (OUD) over their lifetime. Due to substance use-related behaviors, untreated OUD is an obstacle to ending the HIV epidemic, especially in rural states with limited treatment options. In November, 2019, The UAB 1917 HIV Clinic opened an outpatient based opioid treatment (OBOT) clinic one half day a week. The objective of this study is to evaluate clinical outcomes and utilization over 8 months. We hypothesized that approximately 200 PWD would have OUD, many with comorbid stimulant use, and that new referrals would increase over time. Methods: This is a retrospective study PWH at the 1917 clinic from OBOT start until June 2020. Opioid misuse was identified by patient reported illicit use using validated tools and/or ICD9 code in the last 12 months. We stratified PWH to determine the OUD continuum of care for all versus those with comorbid stimulant disorder: OBOT referral, attendance, buprenorphine initiation, and HIV suppression (viral load < 20). We explored changes in clinic utilization following COVID19. Results: A total of 3, 580 patients receive care in the UAB 1917 HIV clinic of whom 40 were identified as having opioid misuse (Fig 1, blue). Overall, 30 patients were referred to OBOT, 25 attended any OBOT visit, 19 were initiated on buprenorphine and 14 (74%) had a VL < 20 in the last 3 months. Over half of patients had comorbid stimulant use disorder (orange). Patients received an average of 3.7 visits (range 1–10) over the study period. Although the number of new referrals did not increase (average 3.8 per month), the overall number of OBOT appointments increased from an average of 12 per month before COVID to 26 per month after March 1. Figure 1. The Opioid Continuum of Care for PWH at the UAB Outpatient Opioid Treatment Clinic (blue) including those with comorbid Stimulant Use Disorder (orange) Conclusion: A surprisingly low percentage of patients report opioid misuse, which likely underestimates the true OUD burden in the Deep South. Stimulant Use Disorder affects over half: an added barrier to HIV suppression. In this small and early assessment, there are multiple missed opportunities for progress along the OUD continuum starting with diagnosis and referral. Yet, even this small clinic has rapidly reached clinical capacity (1/2 day weekly) accelerated by psychosocial needs in the context of COVID19. Disclosures: All Authors : No reported disclosures